A Discourse Analysis of Norminalization in IGBO Language - Ngozi L Dom-Anyanwu (MultiTech Publisher, 2023)
This paper looks at how Igbo people use their language in general interactions. Discourse analysis of Igbo norminalization therefore looks at what and how the Igbo norminals are realize in their interactions both in written and oral forms. The main objective of this study is to indicate and expose the impacts of normalization as well as show how nouns are derived from other word classes in Igbo language. The method used in this study is discourse analysis method which is used to analyze connected speech or writing of the Igbo. Primary and secondary sources are used for data gathering. The study adopts the structural grammar theoretical framework prominently used by Bloomfield in 1914. The paper looks at the processes of forming Igbo nouns from other word classes. The study concludes that norminalization exists in Igbo language discourse and it is derived from word classes like, norminals, noun phrase, verb phrase and even sentences. And this makes Igbo language oral and written form perfect in every discourse.